#### Answer

$\frac{-x+4}{4}$

#### Work Step by Step

$\frac{x+3}{4}$-$\frac{2x-1}{4}$=
$\frac{x+3-(2x-1)}{4}$=$\frac{x+3-2x+1}{4}$=
$\frac{-x+4}{4}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{-x+4}{4}$

$\frac{x+3}{4}$-$\frac{2x-1}{4}$=
$\frac{x+3-(2x-1)}{4}$=$\frac{x+3-2x+1}{4}$=
$\frac{-x+4}{4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.